Effect of Health Education on Knowledge and Perceptions Regarding Cervical Cancer Screening and Prevention among Female Students of a Medical College in Rawalpindi, Pakistan: Pre and Post Analysis - Zia, Aleena; Mashhadi, Syed Fawad; Riasat, Rabia; Aftab, Simal; Sharif, Imtenan; Shahid, Maheen (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate and compare the knowledge and attitude of future female health care providers regarding pap smear screening for cervical cancer at a medical and dental institution in Pakistan. The quality of knowledge of the students was analysed to measure the efficacy of awareness intervention sessions of the students. This was aimed to highlight their role in public awareness and identify the deficit thereof in their training towards practicing preventive community medicine. Study Design: This was a pre and post analysis comparative study. Place and Duration of Study: Conducted at Army Medical College Rawalpindi Pakistan, over an 8-months period from Nov 2019 to Jun 2020. Methodology: A total of 754 responses, pre intervention -401- and one-month later post intervention-353 were collected through a validated questionnaire by convenience sampling. Changes in the knowledge and attitude of students using an independent sample t test were determined one month after 20-minute educational intervention detailing cervical cancer and its screening. Association between course and year of study on the knowledge and attitude scores was determined bycomparing means using ANOVA tables. Results: Comparison of pre and post intervention scores revealed a statistically significant difference in knowledge (p< 0.001)and attitude (p=0.002) with a change in mean knowledge scores from 46.31±15.93 to 74.03±15.71 and mean attitude scores from 45.84±14.37 to 48.86±12.54 after the intervention. MBBS students showed a statistically significant improvement in attitude (p<0.001) than their BDS counterparts (p=0.535). Conclusion: Pre-intervention knowledge and attitude was inadequate. The intervention was successful with a significant increase in scores. Emphasis should be on implementing national HPV vaccination and cervical screening awareness campaigns.